2016
DOI: 10.3991/ijet.v11i09.6127
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Application Mode of MOOC-based Distance Education Mode in Digital Illustration

Abstract: Abstract-with the continuous development of computer technology, online learning has also become a new trend. Noticeably, the MOOC-based distance education mode can meet students' demand for superior teaching resources and assist students to engage in independent study and teachers to change their classroom teaching mode. This paper started from the development status of MOOC and distance education to construct the MOOC platform and design the MOOC-based distance education mode. Then, a control experiment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Educational delivery modes (Cluster 3): Distance education delivery modes (e.g., e-learning, m-learning, online education), and with a specific focus on HE, open learning, and lifelong learning, were the central nodes in this cluster. The publications also argue that MOOCs are inherent to distance education (Zou, 2016) and are "characterized by openness, online and large-scale, all of which are conducive to creating a profound reform in education and teaching, thus significantly affecting higher education" (Liu, 2017, p. 785). Their application for blended learning (Bralić, & Divjak, 2018) or flipped classrooms (Cao, 2018) further makes them popular from a HE perspective.…”
Section: Social Network Analysis Of the Abstractmentioning
confidence: 99%
“…Educational delivery modes (Cluster 3): Distance education delivery modes (e.g., e-learning, m-learning, online education), and with a specific focus on HE, open learning, and lifelong learning, were the central nodes in this cluster. The publications also argue that MOOCs are inherent to distance education (Zou, 2016) and are "characterized by openness, online and large-scale, all of which are conducive to creating a profound reform in education and teaching, thus significantly affecting higher education" (Liu, 2017, p. 785). Their application for blended learning (Bralić, & Divjak, 2018) or flipped classrooms (Cao, 2018) further makes them popular from a HE perspective.…”
Section: Social Network Analysis Of the Abstractmentioning
confidence: 99%
“…The importance of MOOC has received more attention during the last eight years, which is the age of MOOC concept. Researchers have shown that MOOC can contribute to student learning and improve their academic results in all areas (Chauhan, 2015; Follis, 2015;Zou, 2016). Assessing the quality of education becomes one of the main pillars of ranking nations development, several global institutions have adopted different methodologies for evaluating the higher education system around the world.…”
mentioning
confidence: 99%